Damage observations and remedial options for approximately 1500 legged and flat-based liquid storage tanks following the 2016 Kaikōura earthquake. (April 2020) - Yazdanian, Mohsen; Ingham, Jason M.; Lomax, Will; Wood, Regan; Dizhur, Dmytro
Abstract: Detailed inspections of numerous wineries located in New Zealand's Marlborough region were conducted following the 2016 Kaikōura earthquake. The subject region contains a wide variety of wineries with a global reputation for its wine production. Observations documented and discussed herein highlight the post-earthquake performance of the 684 legged and 895 flat-based stainless-steel wine tanks. Damage data revealed that the legs of legged wine tanks are the most vulnerable element of the legged wine tanks. Earthquake-related damage to the anchorage system was the most commonly documented mode of failure for the flat-based tanks. Damage to tanks with different anchorage systems was also investigated herein, where it was noticed that tanks equipped with energy dissipation devices performed much better than other tanks. The comparison of remedial options for the legged wine tanks and flat-based tanks revealed that skirt extension of damaged legged wine tanks and the replacement of these tanks with flat-based tanks was a common procedure that was performed following the recent earthquakes in New Zealand.